Political hypocrisy the mask of power, from Hobbes to Orwell and beyond - Runciman, David (Princeton University Press, 2008)
What kind of hypocrite should voters choose as their next leader? The question seems utterly cynical. But, as David Runciman suggests, it is actually much more cynical to pretend that politics can ever be completely sincere. The most dangerous form of political hypocrisy is to claim to have a politics without hypocrisy. Political Hypocrisy is a timely, and timeless, book on the problems of sincerity and truth in politics, and how we can deal with them without slipping into hypocrisy ourselves. Runciman tackles the problems through lessons drawn from some of the great truth-tellers in modern political thought--Hobbes, Mandeville, Jefferson, Bentham, Sidgwick, and Orwell--and applies his ideas to different kinds of hypocritical politicians from Oliver Cromwell to Hillary Clinton. Runciman argues that we should accept hypocrisy as a fact of politics, but without resigning ourselves to it, let alone cynically embracing it. We should stop trying to eliminate every form of hypocrisy, and we should stop vainly searching for ideally authentic politicians. Instead, we should try to distinguish between harmless and harmful hypocrisies and should worry only about its most damaging varieties. Written in a lively style, this book will change how we look at political hypocrisy and how we answer some basic questions about politics: What are the limits of truthfulness in politics? And when, where, and how should we expect our politicians to be honest with us, and about what?Some images inside the book are unavailable due to digital copyright restrictions.
Keywords: Political ethics; Hypocrisy : Political aspects; Political science : Philosophy